(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Structure, behavior, and decision-making of the entire economy. This includes a national, regional, or global economy with microeconomics, macroeconomics is one of the two most general fields in economics.Macroeconomists study aggregated indicators such as GDP, unemployment rates, and price indices to understand how the whole economy functions. Macroeconomists develop models that explain the relationship between such factors as national income, output, consumption, unemployment, inflation, savings, investment, international trade and international finance. In contrast, microeconomics is primarily focused on the actions of individual agents, such as firms and consumers, and how their behavior determines prices and quantities in specific markets.